Cross-Sectional and Longitudinal Evaluation of the Social Network Use Disorder and Internet Gaming Disorder Criteria - Bouna-Pyrrou, Polyxeni; Aufleger, Birte; Braun, Simona; Gattnar, Manja; Kallmayer, Sofia; Wagner, Helena; Kornhuber, Johannes; Mühle, Christiane; Lenz, Bernd (Frontiers in Psychiatry, 2018)
Background: The inclusion of internet gaming disorder (IGD) as a condition warranting more research in the DSM-5 has led to a rapid increase of research on addictive internet activities. Further evaluation of the criteria for IGD and social network disorder (SND) is needed. Objective: To assess the internal consistency, construct validity, retest-reliability, and long-term stability of SND and IGD criteria in German-speaking cohorts. Method: We conducted total and sex-specific analyses on data from two cross-sectional and longitudinal studies, one sample of 192 participants enriched for internet use and another community-based sample of 2316 individuals. Results: First, independent from assessment setting (online, telephone, on-site) and gender, we found acceptable to good internal consistency for SND and IGD criteria (Cronbach's α 0.690-0.774 for SND and 0.743-0.866 for IGD, respectively). Second, positive Spearman correlations between the sum of affirmed criteria and established scales of pathological internet use (ρ 0.395-0.783) and time spent on the social networking sites or internet gaming (ρ 0.317-0.761) confirmed convergent validity. Moreover, the sum of affirmed criteria related positively to attentional impulsivity (ρmax 0.311), urgency (ρ 0.124-0.200), and neuroticism (ρmax 0.210), and negatively to perseverance (ρ -0.245- -0.098) and conscientiousness (ρmin -0.257). Finally, SND and IGD criteria showed high retest stability (SND ρ 0.653-0.826, IGD ρ 0.714-0.825, respectively). However, participants scored higher on SND and IGD scales during the online compared to the on-site assessment. The 2-year follow-up revealed an increase in affirmed SND and IGD criteria. Conclusion: Our data support good psychometric properties of the SND and IGD criteria and outline the addictive potential of social networking sites.
EVALuna2:211611